Permissive activities in the mechanism of regulation of natural resource relations - Shakhray, Irina S. (Journal of the Belarusian State University. Law, 2022)
The author analyses the content and features of permissive activities in the feld of natural resources. The inﬂuence on the content of permissive legal relations of the plurality of subjects of permissive activities, the multi-stage nature of the procedures for granting the nature usage right and the implementation of other types of activities in this area are studied. Conclusions are formulated about the place in the permissive system of tenders and contracts related to the granting of the nature usage right, hunting and fshing farm. Proposals are made to ensure the consistency of natural resource legislation and legislation on administrative procedures.